ANALISIS KOMPETENSI KEPRIBADIAN GURU PADA MADRASAH ALIYAH ASSALAM POLONGBANGKENG UTARA KABUPATEN TAKALAR - Rurung, Rurung; Siraj, Arifuddin; Musdalifah, Musdalifah (Idaarah: Jurnal Manajemen Pendidikan, 2019)
Abstract: This type of reserch is qualitative. In this study, researchers took the population of Aliyah Madrassah Assalam Timbuseng teachers, which totaled 6 people with a sample of 23 teachers. The results showed that personality competencies, teachers at MA AS-Salam, there are some teachers who meet the criteria that are indicators of personality competency, but there are also some teachers who still lack personality competency. To teachers who have very comptent personalities, students will be very respectful and even feel reluctant to the teacher concerned. In contrast to teachers whose personality competencies are still lacking students will tend to show less respect. The teacher in building personal relationship with students through many ways both in the classroom when the teaching and learning process takes place and outside the classroom. The Madrasah facilitates teachers to take part in activities related to competency enhacement, including by attending teacher upgrading, attending MGBS, and taking courses.